The clinical and pathological spectrum of "inflammatory pseudotumors": extrapulmonary (myofbroblastic and follicular dendritic) Regarding five observations - Vercelli Retta, Jorge; Musé, Miguel I (Cirugía del Uruguay, 2004)
The paper refers to five cases of the so-called inflammatory pseudo tumors, al/ of which were extra pulmonary. Two of the patients had /esions in spleen, two others in pelvic topography relative to bladder, and the remaining one was located in the soft parts of the spermatic chord. Clínica/ history shows that histopatology of these lesions does not conform a single entity, and this has a bearing on evolution and prognosis.